Factor V Leiden paradox and the occurrence of distal vein thrombosis in a large cohort of thrombotic patients. Issue 156 (August 2017) - Campello, Elena; Spiezia, Luca; Dalla Valle, Fabio; Tormene, Daniela; Simioni, Paolo
Highlights: The paradox was limited to heterozygous and homozygous FVL carriers. Double heterozygotes had a clinical presentation intermediate between FVL and prothrombin mutation single carriers. The higher prevalence of isolated distal vein thrombosis in FVL might in part explain the presence of paradox.